Alignment with agility (AWA): centering Indigenous feminisms, living ‘AWAke’, creating a ‘wake’ of change - Catherine E. O’Connor (Cogent Social Sciences)
Extending the empirically informed the critical, feminist, and Indigenist Framework of Historical Oppression, Resilience and Transcendence (FHORT), the purpose of this article is to introduce the concept of living AWAke. An extension of FHORT, living AWAke is distinct from other frameworks because it centers an intersectional, Indigenist approach to gender and its effect on daily life. Systematic and structural oppression insidiously effect every aspect of daily lives; they pose infinite, sometimes subtle, sometimes overt, but always profoundly harmful and intrusive barriers for the wellness of women and other oppressed groups. The FHORT situates resilience (recovering and adapting well after adversity), wellness (holistic well-being), and transcendence (moving beyond and becoming more liberated despite experiencing challenges) within historical oppression (the structures of society impose and perpetuate differential access to wellness and quality of life based on gender, race, socioeconomic status, and other dimensions of diversity). As a component of wellness, resilience, and transcendence, this work extends and transforms the FHORT for an in-depth focus on a critical component of transcendence—AWA. Living AWAke includes living life with alignment (living with intentionality and according to chosen values) with agility (being nimble and responsive to life, which is gendered and constantly shifting; AWA).